Inhibition of the Glycolysis Prevents the Cerebral Infarction Progression Through Decreasing the Lactylation Levels of LCP1 - Zhang, Wei; Xu, Liang; Yu, Zhenfei; Zhang, Meiqi; Liu, Jingquan; Zhou, Jianming (Molecular biotechnology, 2023)
Cerebral infarction (CI), also known as ischemic stroke, has a high incidence rate and mortality rate. The purpose of this study was to investigate the potential effect and mechanism of Lymphocyte cytosolic protein 1 (LCP1) in the CI progression. The middle cerebral artery occlusion (MCAO) treated rats and oxygen–glucose deprivation/reoxygenation (OGD/R) stimulated PC12 cells were used to establish CI model in vivo and in vitro. The cell proliferation and apoptosis was determined by CCK-8 assay and flow cytometry, respectively. Immunoprecipitation and western blot was performed to test the lactylation levels of LCP1. The cells were treated with cycloheximide to determined the protein stability of LCP1. The glucose uptake and lactate production was determined with commercial kits. The extracellular acidification rate were evaluated by Seahorse. The results showed that LCP1 was upregulated in the MCAO rats and OGD/R stimulated PC12 cells. LCP1 knockdown dramatically decreased the neurological score, infarct volume and the brain water content of MCAO rats. Besides, LCP1 knockdown promoted the cell viability while decreased the apoptosis rate of the OGD/R stimulated PC12 cells. Additionally, the global lactylation and lactylation levels of LCP1 was prominently enhanced in vivo and in vitro in cerebral infarction. 2-DG treatment prominently decreased it. In conclusion, inhibiting the glycolysis decreased the lactylation levels of LCP1 and resulted in the degradation of LCP1, which eventually relieved the CI progression.